Impact of trade liberalization on tax revenues and tax structures in developing countries - Karimi, Mohammad (2016)
Trade liberalization tends to be an intrinsic part of structural adjustment programs due to its presumed beneficial effects on growth. However, trade reform policies can have fiscal effects that hinder growth and development. This dissertation takes a critical look at the effect of trade liberalization on taxation in developing countries. The study intends to (a) investigate the impact of trade liberalization on international trade tax revenue in developing countries and examine whether this impact is conditioned by the level of trade liberalization; (b) explore the empirical nexus between trade liberalization and total tax revenues and examine whether this relationship is contingent on the level of trade liberalization and countries’ characteristics (such as level of national income and countries’ dependency on oil revenues) in developing countries; and (c) analyze the impact of trade liberalization on the tax structures in developing countries. For the first and second objectives, a dynamic panel threshold regression approach is utilized on panel data of 103 developing countries covering the period of 1993-2012. While for the third objective, a fixed effects regression framework is performed by using panel data for 97 developing countries over 1993-2012. The findings for the first objective suggest a non-linear relationship between tariff rate and international trade tax revenue and revealing an evidence of potential Laffer curve effect. Concerning the link between trade liberalization and total tax revenues (second objective), the results show a non-linear relationship, implying that the impact of trade liberalization on total tax revenues is negative initially, but when trade openness exceeds the detected threshold level of trade openness, this negative effect will be changed to a significant positive effect. The results further indicate that the relationship between trade liberalization and total tax revenues is contingent on level of national income and oil revenues. As for the third objective, the findings indicate that the impacts of trade liberalization on tax structures are sensitive to the different measures of trade liberalization. While trade openness does not have a significant impact on all kinds of tax shares in developing countries, reduction of tariff rates and WTO membership seems to contribute to the changes in the tax structures in these countries. Inconclusion, trade liberalization seems to play an important role in determining the international trade tax revenue, total tax revenues, and tax structures in developing countries. The findings of this research provide important policy implications for trade liberalization and taxation strategies of developing countries. Generally, providing a favorable environment and infrastructure with a stable trade policy and effective trade regulation is a significant task facing most of the developing countries.